2018
DOI: 10.1080/17518253.2018.1510991
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of bioactive heterocycles using reusable heterogeneous catalyst HClO4–SiO2 under solvent-free conditions

Abstract: We are reporting a simple, efficient and green protocol for the synthesis of chromenes and dihydropyrimidines (products of Knoevenagel and Biginelli reaction, respectively) by the use of silica-supported perchloric acid (HClO 4-SiO 2) as an effective heterogeneous catalyst. Short reaction times, high product yields, simple procedure and reusability of the catalyst are the superior characteristics of this protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In 2018, L. V. Chanu and his co-workers reported an HClO 4 –SiO 2 catalyzed solvent-free synthesis of chromenes by Knoevenagel condensation and dihydro-pyrimidinone via Biginelli-type reaction with β-oxodithioesters as starting compound (Scheme 19). 32 They initiated the Knoevenegel condensation with salicaldehyde 69a (1 mmol) and methyl 3-oxo-3-phenylpropanedithioate 68a (1 mmol) using the HClO 4 –SiO 2 catalyst. The best results were obtained when the reaction temperature was elevated to 80 °C for two hours while using a 5 mol% catalyst in solvent-free conditions.…”
Section: Conventional Heatingmentioning
confidence: 99%
“…In 2018, L. V. Chanu and his co-workers reported an HClO 4 –SiO 2 catalyzed solvent-free synthesis of chromenes by Knoevenagel condensation and dihydro-pyrimidinone via Biginelli-type reaction with β-oxodithioesters as starting compound (Scheme 19). 32 They initiated the Knoevenegel condensation with salicaldehyde 69a (1 mmol) and methyl 3-oxo-3-phenylpropanedithioate 68a (1 mmol) using the HClO 4 –SiO 2 catalyst. The best results were obtained when the reaction temperature was elevated to 80 °C for two hours while using a 5 mol% catalyst in solvent-free conditions.…”
Section: Conventional Heatingmentioning
confidence: 99%
“…Anyway, going on with further bibliographic research, we were surprised to note the reported activity of silica perchloric acid (HClO 4 •SiO 2 ) [33][34][35][36], or silica triflic (trifluoromethanesulfonic) acid [37][38][39], even in the acetalization processes. Potassium bisulfate on silica (KHSO 4 •SiO 2 ) showed good activity too [40], although it was not tested in acetalization processes, until now.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, according to a use-inspired basic research, we judged the employment of these "special" acids to be not justified. Perchloric acid, in particular, features known safety problems on concentration [36], so loading on silica was limited to 0.75 mmol/g [35]. A series of bisulfates never employed in acetalization processes were also considered, namely: sodium (entry 3, Table 2), potassium (entry 4), ammonium (entry 5), and N-Me imidazolium (entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…[57][58][59][60][61][62] Among the various heterocyclic molecules, heterocycles having oxygen are considered as the main class of drugs. [63][64][65][66] Moreover, chromenes, as chemical intermediates, are broadly utilized in numerous industrial formulations including biological and pharmaceutical ones. [63,[67][68][69][70] It is worth mentioning that various approaches have been reported for the synthesis of chromenes.…”
Section: Introductionmentioning
confidence: 99%